Active lakes of Recovery Ice Stream, East Antarctica: a bedrock-controlled subglacial hydrological system. Issue 223 (2014) - Fricker, Helen Amanda; Carter, Sasha P.; Bell, Robin E.; Scambos, Ted
Abstract: A connected system of active subglacial lakes was revealed beneath Recovery Ice Stream, East Antarctica, by ICESat laser altimetry. Here we combine repeat-track analysis of ICESat (2003–09), Operation IceBridge laser altimetry and radio-echo sounding (2011 and 2012), and MODIS image differencing (2009–2011) to learn more about the lake activity history, the surface and bedrock topographic setting of the lakes and the constraints on water flow through the system. We extend the lake activity time series to 2012 for the three lower lakes and capture two major lake drainages. One lake underwent a large deflation between 2009 and 2011 while another lake, which had been continuously filling between 2003 and 2010, started to drain after 2011. Most of the active lakes are located in a 1000 km long bedrock trough under the main trunk of Recovery Ice Stream, whose base is 1500– 2000 m below present-day sea level. The hydrologic system beneath Recovery Ice Stream is controlled by this unusually pronounced bedrock topography, in contrast to most Antarctic systems studied to date, which are controlled by the ice surface topography. Hydrologic connections among the lakes appear to be direct and responsive, and we reproduce the lake activity using a simple subglacial water model. We discuss potential causes of non-steady hydrologic behavior in major Antarctic catchments.